Treatment delay of cancer patients in Indonesia: a reflection from a national referral hospital (Medical Journal of Indonesia, 2021)
BACKGROUND Cancer is a complex disease requiring a multidisciplinary approach in establishing prompt diagnosis and treatment. Treatment in a timely manner is crucial for the outcomes. Hence, this study aimed to provide information on treatment delay including patient and provider delays and its associated factors. METHODS Cancer patients were recruited conveniently in the outpatient clinic of Department of Radiation Oncology, Cipto Mangunkusumo Hospital, Indonesia between May and August 2015. All patients were asked to fill a questionnaire and interviewed in this cross-sectional study. Treatment delay was explored and categorized into patient delay and provider delay. Patient delay could be happened before (patient-delay-1) or after (patient-delay-2) the patient was diagnosed with cancer. Provider delay could be due to physician, system-diagnosis, and system-treatment delays. RESULTS Among 294 patients, 86% patient had treatment delay. Patient delay was observed in 153 patients, and 43% of them had a history of alternative treatment. An older age (p = 0.047), lower educational level (p = 0.047), and history of alternative treatment (p<0.001) were associated with patient delay. Meanwhile, 214 patients had provider delay, and 9%, 36%, and 80% of them experienced physician, system-diagnosis, and system-treatment delays, respectively. All types of provider delay were associated with patient delay (p<0.001). CONCLUSIONS Most of the patient had treatment delay caused by either patient or provider.